Kajian observasi pencemaran lingkungan: Perilaku kebiasaan masyarakat kabupaten Pali menimbun hasil perkebunan karet ke sungai - Aslamiah, Lisa; Surtikanti, Hertien Koosbandiah (Journal of Agrosociology and Sustainability, 2024)
Rubber is one of the plantation commodities which has quite an important role in economic activities in Indonesia. South Sumatra is the largest average contributor to natural rubber production, namely 28.77% of the total national rubber production each year. However, most rubber farmers have a habit of storing and dumping their rubber harvest in rivers. Where the river is the main water body to meet their daily needs. This habit over time will have an impact on environmental pollution. This article aims to provide comprehensive information about the negative impacts of soaking rubber in rivers and provide understanding to the public regarding the impacts and dangers of the habit of soaking rubber in rivers. The research method used is qualitative analysis. The data collection used was primary data through direct observation, filling out questionnaires, interviews with 15 people from the Pali Regency community who live around the river and secondary data through literature study. The results show that the community still practices the habit of soaking rubber agricultural products in rivers in Pali Regency, despite a lack of awareness and knowledge about the negative impacts they cause. The conclusions of this research indicate the need for efforts to increase community awareness and knowledge about the negative impacts of the rubber soaking habit. Through this article, it is hoped that it can open people's eyes to the risks and consequences associated with this habit so that it can create a healthy environment and improve the quality of rubber agricultural products in the future.